PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT.SD NEGERI 01 SEISIMUJUR - Ardana, Natasya Dita; Tambunan, Husna Parluhutan; Lubis, Wildansyah; Ananda, Lala Jelita; Prawijaya, Septian (JURNAL KELUARGA SEHAT SEJAHTERA, 2024)
This study aims to obtain information on whether or not there is a determinant of the learning model Snowball Throwing on the resultant learning of IPAS class IV UPT.SD Negeri 01 Seisimujur students. This type of research is quantitative. The location of this research was at UPT.SD Negeri 01 Seisimujur. The implementation time of this research was carried out in the 2023/2024 school year. The population for this study was the entire class IV UPT.SD Negeri 01 Seisimujur. The sample in this study amounted to 62 students composed of class IVA being the experimental class with 31 students and class IVB being the control class with 31 students. In the resultant analysis, the resultant data of students' IPAS learning obtained the average (mean) after treatment for the experimental class through the Snowball Throwing learning model was a pretest score of 55.34 and a posttest of 66.94. While students in the control class using the conventional learning model obtained a mean pretest score of 40.81 and a posttest of 50.65. So the group of students who received the Snowball Throwing learning model treatment had a higher mean score when compared to without using the Snowball Throwing learning model.